Strategi Inklusif Untuk Mewujudkan Ketahanan Pangan di Desa Sembalun - Puspita Dewi, Maya (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
Food security is a crucial element in achieving sustainable development, especially in agrarian regions vulnerable to climate change. Desa Sembalun, Lombok Timur, despite its significant agricultural potential as a producer of garlic, potatoes, and carrots, faces challenges such as monoculture dependency, limited empowerment of women, and weak institutional support. This study aims to develop an inclusive community-based food security governance model through crop diversification, strengthening local institutions, and promoting active participation of women. Using the Participatory Action Research (PAR) method, the research involved 30 informants, including farmers, community leaders, and local government representatives, through in-depth interviews, focus group discussions, and observations. The findings reveal that 75% of farmers rely on monoculture, while only 25% have adopted crop diversification. Women play a significant role in food production but their participation in decision-making processes remains low at 20%. Community gardens demonstrate significant potential in supporting food security, but their management lacks adequate institutional support. This study recommends strengthening local institutions, empowering women, and promoting crop diversification as primary strategies to build inclusive and sustainable food security in Desa Sembalun, serving as a potential model for other agrarian regions.